Connexin43 hemichannels: A potential drug target for the treatment of diabetic retinopathy. Issue 8 (August 2019) - Mugisho, Odunayo O.; Green, Colin R.; Zhang, Jie; Acosta, Monica L.; Rupenthal, Ilva D.
Highlights: Limitations of current DR therapies highlight the need for targeting upstream mechanisms. Connexin43 hemichannel blockers are efficacious in treating various vascular diseases. Connexin43 hemichannel blockers inhibit ATP release to stop inflammasome activation. Connexin43 hemichannel blockers can treat the underlying inflammation in DR. Abstract : Diabetic retinopathy (DR) is a chronic vascular disease of the retina that causes vision loss in patients with type 1 and type 2 diabetes, and is associated with vascular dysfunction and occlusion, retinal oedema, haemorrhage and inadequate growth of new blood vessels. Current DR therapies primarily target downstream, later-stage vascular defects with a significant proportion of diabetic macular oedema patients being non-responders. Moreover, other evidence suggests that prolonged use of therapies targeting vascular endothelial growth factor (VEGF) might be associated with increased onset of geographic atrophy and retinal ganglion cell death. It is therefore highly desirable to prevent the onset of DR or arrest its progression at a stage preceding the appearance of more-advanced pathology by targeting upstream disease mechanisms. Connexin43 hemichannels play a part in the pathogenesis of chronic inflammatory diseases, including inflammasome pathway activation; and hemichannel block has been shown to alleviate vascular leak and inflammation. This review discusses the inflammatory changes occurring in DR as well as current therapies and their limitations. It then focuses on the role of connexin43 in DR, providing evidence for the utility of connexin43 hemichannel blockers as novel therapeutics for DR treatment.